We are here to help : listening to the voices of the Non-Enrolment Truancy Service education advisers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Smales, Murray (Massey University, 2002)
Truancy and school alienation have been problematic for education since the establishment of schools and even before schooling became compulsory in 1877. With the advent of "Tomorrow's Schools" in 1989 pressure was applied to school Boards of Trustees to deal with truancy (Education Act, 1989, Part 111, Section 31.3). School boards of trustees expressed concern as to the legitimacy of this role and further expressed their anxiety about the lack of resources schools had to call upon to deal with truancy problems. In 1996 the Ministry of Education established the Non-Enrolment Truancy Service (NETS) to work in the field, returning non-enrolled truants to education. The New Zealand House of Representatives "Inquiry into Children in Education At Risk Through Truancy and Behavioural Problems" (1995) conceded that truancy in New Zealand was wide spread throughout the country. Truancy tends to have the greatest affect upon students and families who are confronted with difficult economic, social, cultural and family challenges Therefore truancy is not just about education but is embedded in the social and economic fabric of society. This study aimed to examine the work, explore the beliefs and investigate the issues raised by Education Advisers whose task it was to return non-enrolled students to education. To enable this to be achieved a multi-case, multi-site case study approach was used incorporating the use of a national questionnaire and in-depth interviews with Education Advisers. The findings of the study revealed there was confusion about the role Education Advisers were expected to fulfil. Education Advisers who had previous experience in the education sector appeared to have advantages over their colleagues who had previously been in the non-education sector. The study highlighted the variety of strategies used by Education Advisers in their attempts to return students to education. However, Education Advisers reported there were barriers that impinged upon their work as they attempted to return students to education. These included school personnel, curriculum, students and their families, government agencies and bureaucracy. Education Advisers identified training and professional development as requiring consideration by NETS management, while the concept of supervision appeared problematic. Ultimately this study shows that truancy is not just an educational issue. Truancy is about social issues, socio-economics, culture and the educational environment. While the Non-Enrolment Truancy Service is successful in their endeavours to return non-enrolled students to education, to successfully retain non-enrolled students in education requires a well resourced collaborative, multi-agency approach to address the issues that contribute to truancy.
Irregular pagination: pg 143 missing - original checked - blank.
Keywords: New Zealand; School attendance